2018
DOI: 10.1515/jcim-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, bioactivity: suggestion of Ceratonia siliqua L. as neurodegenerative disease therapy

Abstract: Carob tree (Ceratonia siliqua L.) is one of the most widespread medicinal plants in the Mediterranean area. Traditionally, it was cultivated for its ethnopharmacological benefits and, more especially, for the seeds, which served as unit of measurement of jewelers "carat." Hence, in the last half-century, numerous studies reported a wide range of phytoconstituents contained in all parts of Ceratonia siliqua such as phenolic compounds, flavonoids, tannins, anthocyanins, alkaloids, glycosides, proteins and minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 59 publications
0
12
0
2
Order By: Relevance
“…Furthermore, the presence of biomolecules such us phenolic compounds, flavonoids, tannins, and anthocyanins in carob pods may have beneficial effects on human and animal health. Numerous studies reported that the extracts of carob exhibit an antioxidant, antidiarrheal, antibacterial, antifungal, anti-inflammatory, antidiabetic activities, and also hepatoprotective and antiproliferative effects ( Custodio et al, 2011 ; Kotrotsios et al, 2012 ; Lakkab et al, 2018 ; Ben Ayache et al, 2020 ). Carob and carob byproducts have been studied previously as a local alternative feed and to prevent and treat diarrhea and as anthelmintic in geese ( Sahle et al, 1992 ), broiler chicken ( Ortiz et al, 2004 ), fish ( Fadel et al, 2017 ), quail ( Calislar and Kaplan, 2017 ) and sheep ( Saratsi et al, 2020 ) diets.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of biomolecules such us phenolic compounds, flavonoids, tannins, and anthocyanins in carob pods may have beneficial effects on human and animal health. Numerous studies reported that the extracts of carob exhibit an antioxidant, antidiarrheal, antibacterial, antifungal, anti-inflammatory, antidiabetic activities, and also hepatoprotective and antiproliferative effects ( Custodio et al, 2011 ; Kotrotsios et al, 2012 ; Lakkab et al, 2018 ; Ben Ayache et al, 2020 ). Carob and carob byproducts have been studied previously as a local alternative feed and to prevent and treat diarrhea and as anthelmintic in geese ( Sahle et al, 1992 ), broiler chicken ( Ortiz et al, 2004 ), fish ( Fadel et al, 2017 ), quail ( Calislar and Kaplan, 2017 ) and sheep ( Saratsi et al, 2020 ) diets.…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson's disease is characterized by tremor, rigidity, bradykinesia, and postural instability (Daviaud et al, 2013;Gaki and Papavassiliou, 2014). Phytochemical compounds of Ceratonia siliqua parts display several neuropharmacological effects mostly related to oxidative damage in body system (Lakkab et al, 2018). Custodio et al, (2015) reported the leaf and stem bark samples had strong activity against acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE).…”
Section: Neuropharmacological Effectmentioning
confidence: 99%
“…Modern research followed traditional knowledge and dozens of studies were published to date about dozens of medicinal activities of Carob’s various products, including its extracts and single natural products. Consequently, many review articles that summarize the research articles can also be found [ 7 , 8 , 9 , 10 ]. However, one of the best review articles about Carob’s composition has been published by K. Rtibi et al, where they focus on Carob-derived treatments of the gastrointestinal tract [ 11 ].…”
Section: Introductionmentioning
confidence: 99%